2020
DOI: 10.1126/sciadv.abc4959
|View full text |Cite
|
Sign up to set email alerts
|

Halide perovskite nanocrystal arrays: Multiplexed synthesis and size-dependent emission

Abstract: Halide perovskites have exceptional optoelectronic properties, but a poor understanding of the relationship between crystal dimensions, composition, and properties limits their use in integrated devices. We report a new multiplexed cantilever-free scanning probe method for synthesizing compositionally diverse and size-controlled halide perovskite nanocrystals spanning square centimeter areas. Single-particle photoluminescence studies reveal multiple independent emission modes due to defect-defined band edges w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 52 publications
(60 reference statements)
0
60
0
Order By: Relevance
“…The crystallization process was highly relevant to the surface roughness, interfacial interactions, as well as solution properties. [ 69 ] We showed that when PDA templates with a smaller size (≈10 µm) and smooth surface ( R q < 20 nm) were employed, the perovskite microcrystals could become larger (>4 µm size), with less crystals covering each microdot (Figure 6F and Figure S8C, Supporting Information). Besides, the MA 3 Bi 2 Br 9 QDs were also successfully patterned through dewetting of the non‐polar toluene solution, although only a small amount of solution was observed to leave on the PDA surface (Figure 6G).…”
Section: Resultsmentioning
confidence: 99%
“…The crystallization process was highly relevant to the surface roughness, interfacial interactions, as well as solution properties. [ 69 ] We showed that when PDA templates with a smaller size (≈10 µm) and smooth surface ( R q < 20 nm) were employed, the perovskite microcrystals could become larger (>4 µm size), with less crystals covering each microdot (Figure 6F and Figure S8C, Supporting Information). Besides, the MA 3 Bi 2 Br 9 QDs were also successfully patterned through dewetting of the non‐polar toluene solution, although only a small amount of solution was observed to leave on the PDA surface (Figure 6G).…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 37 ] Copyright 2020, American Association for the Advancement of Science.…”
Section: Fabrication Of Nms By Dpnmentioning
confidence: 99%
“…By further designing appropriate inks, single‐crystal halide perovskite nanoarrays were patterned over a large‐area (square centimeter) via PPL with great control over composition and size (Figure 5 2020‐2). [ 37 ] Unlike molecular or polymer inks used in conventional PPL, a liquid organic ink containing halide perovskite precursors dissolved in a mixture of dimethyl sulfoxide (DMSO) and sulfolane was used and applied to the array of PDMS pyramidal pens. Due to high surface tension and low viscosity, the ink accumulates around the base of each pyramid and serves as a reservoir for continuous inking as subsequent features are deposited.…”
Section: Fabrication Of Nms By Dpnmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all‐inorganic perovskite nanocrystals (PNCs) of diverse shapes (e.g., nanocubes, [11] nanowires (NWs), [12] nanosheets (NSs) [13] and heterostructures [9, 14] ), synthesized by several impressive synthetic routes (e.g., ligand‐assisted reprecipitation (LARP), [15] post‐treatment, [16] confined growth in inorganic matrix, [11c] etc. ), have emerged as building blocks for constructing PNC‐based optoelectronic devices [17, 18] . The stability of PNCs against external stimuli (e.g., water, polar solvents, light) is the key to their utility for practical applications.…”
Section: Introductionmentioning
confidence: 99%